PENGARUH PEMBERIAN SILASE LIMBAH IKAN TERHADAP LEMAK ABDOMINAL DAN LEMAK DAGING PADA BEBEK PEDAGING - Reni Rakhmawati; Mei Sulistyoningsih; Atip Nurwahyunani; Karina Rinanda Priscilla (JURNAL ILMIAH AGRINECA, 2021)
The purpose of this study to determine the effect of giving silage of fish waste to the level of meat fat and the abdominal fat of duck in Magelang. The role of duck farming is very important to provide the protein of Indonesian people for meat and eggs. The use of feeding ingredients that are easily available at relatively cheaper prices but still good nutritional content for the production, one of them is by utilizing silage of fish waste. Fish waste silage also contains the necessary ingredients for ducks. The design used in this study was a completely randomized design (CRD). The study consisted of 3 treatments there is P0 (control), P1 (fish silage 5%), P2 (fish silage 10%), and 4 repetitions. The analysis using one-way ANOVA with a level of 5%, if there is a difference, then Duncan's Multiple Distance Test is performed. The results showed that silage application of fish waste did not significantly affect the fat content of meat (P> 0.05). There was no significant effect on abdominal fat levels (P> 0.05). The result showed that the addition of fish silage food resulted in the normal level of meet fat and abdominal fat.